Intelligent quantum information processing - Bhattacharyya, Siddhartha 1975-; Cruz-Aceves, Ivan; Deyasi, Arpan 1978-; Debnath, Pampa; Mahapatra, Rajarshi (Quantum machine intelligence series, 2024)
The book discusses the foundations of intelligent quantum information processing applied to several real-life engineering problems, including intelligent quantum systems, intelligent quantum communication, intelligent process optimization, and intelligent quantum distributed networks.This book:• Showcases a detailed overview of different quantum machine learning algorithmic frameworks.• Presents real-life case studies and applications.• Provides an in-depth analysis of quantum mechanical principles.• Provides a step-by-step guide in the build-up of quantum inspired/quantum intelligent information processing systems.• Provides a video demonstration on each chapter for better understanding.It will serve as an ideal reference text for graduate students and academic researchers in fields such as electrical engineering, electronics and communication engineering, computer engineering, and information technology